Faktor Risiko Kejadian Malaria pada Masyarakat Wilayah Pertambangan: Literature Review - Risva Aprina Fitri Lestari; Hamzah Hasyim; Novrikasari Novrikasari (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Globally, nearly 85% of malaria cases occur in nineteen Indian sub-Saharan African countries.Tropical and subtropical countries are endemic areas for this disease because they have a rainy season that provides a high availability of clean water, where vector mosquitoes can lay eggs and breed.. KForest activities such as agriculture, logging and gold mining are considered high risk occupations for exposure to malaria, this is because forest workers, especially miners and loggers, often spend weeks to months at work..This article uses a literature review approach with a cross-sectional study design. Articles are searched through electronic databases systematically onScience Direct, Malaria Journal, and PubMedpublished in the last 10 years and taken between the years (2013-2022) using the keywords (risk factorAND malaria AND “mine workers). Based on the results of data extraction from search engines of the Science Direct, Malaria Journal, and PubMed methods, there are 15 journals selected based on inclusion criteria. FactorsThe risk of malaria in mining area communities is age, gender, education, knowledge, behavior, attitudes, and environmental conditions.This study serves as a baseline for assessing the impacts of mining activities in relation to future vector control interventions.Malaria elimination efforts can be accelerated by targeting improvements in treatment practices, diagnosis, and reporting to private pharmacies, private clinics, and grocery stores. Programs should also seek to increase awareness and understanding of malaria among at-risk populations, in particular the importance of using preventive measures and following a comprehensive antimalarial treatment program.